2011
DOI: 10.1111/j.1748-1716.2011.02275.x
|View full text |Cite
|
Sign up to set email alerts
|

The hexosamine biosynthetic pathway can mediate myocardial apoptosis in a rat model of diet-induced insulin resistance

Abstract: The main finding of this study is that increased apoptosis in hyperglycaemic/insulin-resistant hearts can also be mediated through HBP-induced BAD O-GlcNAcylation and greater formation of BAD-Bcl-2 dimers (pro-apoptotic).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Treatment with hesperetin and glibenclamide in diabetic rats showed significant reduction in hexoses due to improved glycemic control. The level of hexosamine, increased significantly in the plasma and tissues of diabetic rats which may be due to insulin deficiency, this leads to depressed utilization of glucose by insulin-dependent pathway, thereby enhancing the formation of hexose and hexosamine [12].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with hesperetin and glibenclamide in diabetic rats showed significant reduction in hexoses due to improved glycemic control. The level of hexosamine, increased significantly in the plasma and tissues of diabetic rats which may be due to insulin deficiency, this leads to depressed utilization of glucose by insulin-dependent pathway, thereby enhancing the formation of hexose and hexosamine [12].…”
Section: Discussionmentioning
confidence: 99%
“…Total O-GlcNAc expression was evaluated by SDS-PAGE as described previously (51,52). Briefly, frozen heart and liver tissues were homogenized with modified ice-cold RIPA buffer, and the supernatant was centrifuged twice at 13,000 g for 10 min at 4°C and then stored at Ϫ80°C until further use.…”
Section: Methodsmentioning
confidence: 99%
“…Nonoxidative glucose pathways include the formation of advanced glycation end products (AGEs), the hexosamine biosynthetic pathway (HBP), and (in part) the pentose phosphate shunt. Previous studies have indicated greater oxidative stress and increased flux through these pathways in obesity (48,51,52); however, the interaction among these pathways is not well understood, nor is it clear how they are impacted by G6PD deficiency. A decrease in oxidant stress in G6PD-deficient myocardium could decrease flux through other nonoxidative pathways of glucose metabolism, resulting in an overall beneficial effect on cardiac structure and function (16,21).…”
mentioning
confidence: 99%
“…These variations mediate the clock-dependent regulation of OGlcNAc transferase and O-GlcNAcase levels and nutrient metabolism and uptake. This would involve the coordinated regulation of the hexosamine biosynthetic pathway and play an important role in not only insulin resistance [103] but also myocardial apoptosis in the diet-induced insulin resistant rat [104] which in turn conversely depends critically on an adequate dark-phase. Any stress could increase flux through the HBP, leading to detrimental effects on the level of the cardiomyocyte [29,104].…”
Section: Active Phase Inactive Phasementioning
confidence: 99%
“…This would involve the coordinated regulation of the hexosamine biosynthetic pathway and play an important role in not only insulin resistance [103] but also myocardial apoptosis in the diet-induced insulin resistant rat [104] which in turn conversely depends critically on an adequate dark-phase. Any stress could increase flux through the HBP, leading to detrimental effects on the level of the cardiomyocyte [29,104]. As the O-GlcNAcylation of proteins show clear circadian patterns and is high during the active phase and low during the inactive phase, it is thus proposed to have major consequences in the rat model of insulin resistance [93].…”
Section: Active Phase Inactive Phasementioning
confidence: 99%